1998
DOI: 10.1017/s0022215100142124
|View full text |Cite
|
Sign up to set email alerts
|

An endoscopic approach to the deviated nasal septum – a preliminary study

Abstract: The authors have used the nasal endoscope for the precise identification of pathological abnormalities of the nasal septum in relation to the lateral nasal wall including the osteo-meatal complex and in its ultraconservative management. The aim of the study was to compare the efficacies of endoscope-aided septoplasty (EAS) over traditional septoplasty (TS) in treating the pathological septum and turbinates, performed in 30 cases each. The subjective assessment was carried out by visual analogue scores and obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 11 publications
3
38
0
1
Order By: Relevance
“…Nayak et al and Jain et al also reported similar incidence of lateral nasal wall pathologies in their respective studies. 6,7 The chief complaint of the patients in our study was nasal obstruction reported by 76 (76%) patients, followed by headache in 40%, nasal discharge in 38%, snoring in 24%, hyposmia in 10% and epistaxis in 5%. Other studies have also reported similar symptoms.…”
Section: Discussionmentioning
confidence: 59%
“…Nayak et al and Jain et al also reported similar incidence of lateral nasal wall pathologies in their respective studies. 6,7 The chief complaint of the patients in our study was nasal obstruction reported by 76 (76%) patients, followed by headache in 40%, nasal discharge in 38%, snoring in 24%, hyposmia in 10% and epistaxis in 5%. Other studies have also reported similar symptoms.…”
Section: Discussionmentioning
confidence: 59%
“…This is comparable to other studies like In Nayak et al study (1998); age group in traditional group ranged from 17-58 years with mean of 28 years and in endoscopic group age ranged from 18-52 years with mean of 24 years. 6 Nayak et al (2002) study shows age range 6-54 years with mean 26.4 years. 7 The high incidence in 2 nd to 4 th decade of age group could be due to the fact that people in their active period of life are more prone to external injuries, hence likely to present with deviated nasal septum and are concerned with their physical status.…”
Section: Discussionmentioning
confidence: 99%
“…This result is comparable to a study conducted by Nayak et al, on 60 patients of whom, 47 patients (78.3%) had complaint of nasal obstruction, 46 patients (76.66%) had headache, 27 patients (45.00%) had rhinorrhoea, 35 patients (58.33%) had post nasal discharge and 5 patients (8.33%) had hyposmia. 7 In another study conducted by Aranachlam et al, nasal obstruction was the predominant complaint present in 74% patients. 8 In the present study, all the patients were discharged on the 2 nd postoperative day after pack removal and followed up on the 7 th post op day and weekly thereafter for one month.…”
mentioning
confidence: 89%